Psychological status in female carriers of premutation FMR1 allele showing a complex relationship with the size of CGG expansion. (17th February 2014) - Loesch, D. Z.; Bui, M. Q.; Hammersley, E.; Schneider, A.; Storey, E.; Stimpson, P.; Burgess, T.; Francis, D.; Slater, H.; Tassone, F.; Hagerman, R. J.; Hessl, D.
Abstract We utilized a sample of 299 adult females aged between 19 and 86 years, carrying fragile X mental retardation (FMR1) alleles with small CCG expansions ranging from 50 to 141 repeats to analyse the relationships between psychological symptoms as assessed by the Symptom Checklist‐90‐Revised (SCL‐90‐R) and the size of the CGG repeat in the FMR1 gene. There were highly significant (negative) correlations between the size of the CGG repeat and a great majority of SCL‐90‐R subscale scores and all the global indices, suggesting that carriers of premutations in the mid‐size CGG repeat range may be at greatest risk for the development of psychiatric disorder.